The Role of Motivation and Reference Group on Functional Food Consumption Behavior - Retnaningsih Retnaningsih; Rahmat Junedi (Journal of Consumer Sciences, 2024)
The advancement of food science and technology has encouraged the development of functional foods in Indonesia. This study aimed to examine the influence of motivation and reference groups on functional food consumption behavior. This cross-sectional research involved 204 active students of IPB University who were selected using the simple random sampling technique. The data were analyzed using descriptive and inferential data analysis. The linear regression tests revealed that pocket money, reference groups, and motivation positively affected the frequency of functional food consumption. In addition, motivation had a significant positive effect on the number of types of functional foods consumed. The results showed that students' motivation to consume functional foods was low. In light of these findings, the government should actively promote the consumption of functional foods by regulating the prices of functional food sources in the market. Universities and industry producers must collaborate to conduct extensive outreach and education to effectively disseminate information about functional foods.